2014
DOI: 10.3390/en7128217
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Energy Harvesting from Macroalgae—Innovative Integration of Drying, Gasification and Combined Cycle

Abstract: State-of-the-art integrated macroalgae utilization processes, consisting of drying, gasification, and combined cycle, are proposed and their performance with respect to energy efficiency are evaluated. To achieve high exergy efficiency, the integration is performed through two main principles: exergy recovery and process integration. Initially, the energy involved in one process is recirculated intensively through exergy elevation and effective heat coupling. Furthermore, the unrecoverable energy from one proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Conventional biomass gasification processes require dry feedstock (Guan et al 2012a;Smith and Ross 2016), and the energy required for drying may make it unviable energetically, but integration of drying and gasification processes could reduce overall energy input (Aziz et al 2014), and the use of solar drying could allow gasification to be net energy positive (Aresta et al 2005). Supercritical water gasification (SCWG) is an alternative gasification technology for the conversion of high moisture biomass and hydrothermal gasification is seen as a potential processing method for wet carbohydrate-rich biomass, such as macroalgae (Suutari et al 2015).…”
Section: Gasificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional biomass gasification processes require dry feedstock (Guan et al 2012a;Smith and Ross 2016), and the energy required for drying may make it unviable energetically, but integration of drying and gasification processes could reduce overall energy input (Aziz et al 2014), and the use of solar drying could allow gasification to be net energy positive (Aresta et al 2005). Supercritical water gasification (SCWG) is an alternative gasification technology for the conversion of high moisture biomass and hydrothermal gasification is seen as a potential processing method for wet carbohydrate-rich biomass, such as macroalgae (Suutari et al 2015).…”
Section: Gasificationmentioning
confidence: 99%
“…Rowbotham et al (Rowbotham et al 2013) have suggested that thermochemical processing methods, such as gasification and hydrothermal liquefaction, are more applicable and versatile treatment options than anaerobic digestion and fermentation, due to the technological difficulties associated with treatment and refining to liquid fuels of complex, heterogeneous, multi-component feedstocks, such as seaweed. (Aziz et al 2014), However, Smith and Ross (2016) reported that the high chlorine, ash and alkali content, low calorific value and high moisture content make macroalgae not only unattractive option for combustion, but also gasification without extensive pre-treatment, and as a consequence, the majority of research into utilising macroalgae as a biofuel has focused on the production of biogas by anaerobic digestion.…”
Section: Gasificationmentioning
confidence: 99%
“…Besides the high potential in the pharmaceuticals, industrial materials, and food production, microalgae own a high potential for the energy source [40]. Among other biomasses, microalgae are very exceptional due to its excellent growth rate, ability to grow in a harsh environment, and highly efficient solar energy conversion [4]. Currently, many products of fuel are derived from the microalgae, including bio-oil, biohydrogen, and biodiesel [41].…”
Section: The Characteristics Of Microalgae As Energy Sourcementioning
confidence: 99%
“…Several parameters need to be accomplished for the future energy carrier, including the simple production method, high energy density, and environmentally benign performance. To this, the hydrogen (H 2 ) has the promising potential as an energy carrier [4]. Under the ambient condition, H 2 owns high gravimetric energy density (120 MJ kg À1 ), much higher than gasoline or natural gas, which leads to the extensive heat capacity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The raw wet coal is ground into small particles before being fed to the dryer. A fluidized bed or rotary dryer may be used, considering solid mixing, heat and mass transfer, and temperature uniformity [18,19]. The CO 2 -rich exhaust gas from the power generation module is fed to the dryer as the drying medium.…”
Section: Computational Modeling Of Palm Kernel Shell Co-firingmentioning
confidence: 99%